Development of Human Breast Milk Microbiota-Associated Mice as a Method to Identify Breast Milk Bacteria Capable of Colonizing Gut - Wang, Xiaoxin; Lu, Huifang; Feng, Zhou; Cao, Jie; Fang, Chao; Xu, Xianming; Zhao, Liping; Shen, Jian (Frontiers in Microbiology, 2017)
Human breast milk is recognized as one of multiple important sources of commensal bacteria for infant gut. Previous studies searched for the bacterial strains shared between breast milk and infant feces by isolating bacteria and performing strain-level bacterial genotyping, but only limited number of milk bacteria were identified to colonize infant gut, including bacteria from Bifidobacterium, Staphylococcus, Lactobacillus, and Escherichia/Shigella. Here, to identify the breast milk bacteria capable of colonizing gut without the interference of bacteria of origins other than the milk or the necessity to analyze infant feces, normal chow-fed germ-free mice were orally inoculated with the breast milk collected from a mother two days after vaginal delivery. According to 16S rRNA gene-based denaturant gradient gel electrophoresis and Illumina sequencing, bacteria at > 1% abundance in the milk inoculum were only Streptococcus (56.0%) and Staphylococcus (37.4%), but in the feces of recipient mice were Streptococcus (80.3 ± 2.3%), Corynebacterium (10.0 ± 2.6 %), Staphylococcus (7.6 ± 1.6%) and Propionibacterium (2.1 ± 0.5%) that were previously shown as dominant bacterial genera in the meconium of C-section-delivered human babies; the abundance of anaerobic gut-associated bacteria, Faecalibacterium, Prevotella, Roseburia, Ruminococcus and Bacteroides, was 0.01% - 1% in the milk inoculum and 0.003% - 0.01% in mouse feces; the abundance of Bifidobacterium spp. was below the detection limit of Illumina sequencing in the milk but at 0.003% - 0.01% in mouse feces. The human breast milk microbiota-associated mouse model may be used to identify additional breast milk bacteria that potentially colonize infant gut.